European Nucleotide Archive in 2016. Issue Volume 45:Issue D1(2017) (28th November 2016) - Toribio, Ana Luisa; Alako, Blaise; Amid, Clara; Cerdeño-Tarrága, Ana; Clarke, Laura; Cleland, Iain; Fairley, Susan; Gibson, Richard; Goodgame, Neil; ten Hoopen, Petra; Jayathilaka, Suran; Kay, Simon; et al.
Abstract: The European Nucleotide Archive (ENA; http://www.ebi.ac.uk/ena ) offers a rich platform for data sharing, publishing and archiving and a globally comprehensive data set for onward use by the scientific community. With a broad scope spanning raw sequencing reads, genome assemblies and functional annotation, the resource provides extensive data submission, search and download facilities across web and programmatic interfaces. Here, we outline ENA content and major access modalities, highlight major developments in 2016 and outline a number of examples of data reuse from ENA.